Differential coupling of self-renewal signaling pathways in murine induced pluripotent stem cells. - Luca Orlando; Yolanda Sanchez-Ripoll; James Foster; Heather Bone; Claudia Giachino; Melanie J Welham (PLoS ONE)
The ability to reprogram somatic cells to induced pluripotent stem cells (iPSCs), exhibiting properties similar to those of embryonic stem cells (ESCs), has attracted much attention, with many studies focused on improving efficiency of derivation and unraveling the mechanisms of reprogramming. Despite this widespread interest, our knowledge of the molecular signaling pathways that are active in iPSCs and that play a role in controlling their fate have not been studied in detail. To address this shortfall, we have characterized the influence of different signals on the behavior of a model mouse iPSC line. We demonstrate significant responses of this iPSC line to the presence of serum, which leads to profoundly enhanced proliferation and, depending on the medium used, a reduction in the capacity of the iPSCs to self-renew. Surprisingly, this iPSC line was less sensitive to withdrawal of LIF compared to ESCs, exemplified by maintenance of expression of a Nanog-GFP reporter and enhanced self-renewal in the absence of LIF. While inhibition of phosphoinositide-3 kinase (PI3K) signaling decreased iPSC self-renewal, inhibition of Gsk-3 promoted it, even in the absence of LIF. High passages of this iPSC line displayed altered characteristics, including genetic instability and a reduced ability to self-renew. However, this second feature could be restored upon inhibition of Gsk-3. Collectively, our data suggest modulation of Gsk-3 activity plays a key role in the control of iPSC fate. We propose that more careful consideration should be given to characterization of the molecular pathways that control the fate of different iPSC lines, since perturbations from those observed in naïve pluripotent ESCs could render iPSCs and their derivatives susceptible to aberrant and potentially undesirable behaviors.